Fruit Morphology and Ripening-Related QTLs in a Newly Developed Introgression Line Collection of the Elite Varieties ‘Védrantais’ and ‘Piel de Sapo’ - Miguel Santo Domingo; Carlos Mayobre; Lara Pereira; Jason Argyris; Laura Valverde; Ana Montserrat Martín-Hernández; Jordi Garcia-Mas; Marta Pujol (Plants, 2022)
Melon is an economically important crop with widely diverse fruit morphology and ripening characteristics. Its diploid sequenced genome and multiple genomic tools make this species suitable to study the genetic architecture of fruit traits. With the development of this introgression line population of the elite varieties ‘Piel de Sapo’ and ‘Védrantais’, we present a powerful tool to study fruit morphology and ripening traits that can also facilitate characterization or pyramidation of QTLs in inodorous melon types. The population consists of 36 lines covering almost 98% of the melon genome, with an average of three introgressions per chromosome and segregating for multiple fruit traits: morphology, ripening and quality. High variability in fruit morphology was found within the population, with 24 QTLs affecting six different traits, confirming previously reported QTLs and two newly detected QTLs, FLQW5.1 and FWQW7.1. We detected 20 QTLs affecting fruit ripening traits, six of them reported for the first time, two affecting the timing of yellowing of the rind (EYELLQW1.1 and EYELLQW8.1) and four at the end of chromosome 8 affecting aroma, abscission and harvest date (EAROQW8.3, EALFQW8.3, ABSQW8.3 and HARQW8.3). We also confirmed the location of several QTLs, such as fruit-quality-related QTLs affecting rind and flesh appearance and flesh firmness.